Effect of time to initiation of postoperative radiation therapy on survival in surgically managed head and neck cancer. Issue 24 (25th August 2017) - Graboyes, Evan M.; Garrett‐Mayer, Elizabeth; Ellis, Mark A.; Sharma, Anand K.; Wahlquist, Amy E.; Lentsch, Eric J.; Nussenbaum, Brian; Day, Terry A.
Abstract : BACKGROUND: The objective of this study was to determine the effects of National Comprehensive Cancer Network (NCCN) guideline–adherent initiation of postoperative radiation therapy (PORT) and different time‐to‐PORT intervals on the overall survival (OS) of patients with head and neck squamous cell carcinoma (HNSCC). METHODS: The National Cancer Data Base was reviewed for the period of 2006‐2014, and patients with HNSCC undergoing surgery and PORT were identified. Kaplan‐Meier survival estimates, Cox regression analysis, and propensity score matching were used to determine the effects of initiating PORT within 6 weeks of surgery and different time‐to‐PORT intervals on survival. RESULTS: This study included 41, 291 patients. After adjustments for covariates, starting PORT >6 weeks postoperatively was associated with decreased OS (adjusted hazard ratio [aHR], 1.13; 99% confidence interval [CI], 1.08‐1.19). This finding remained in the propensity score–matched subset (hazard ratio, 1.21; 99% CI, 1.15‐1.28). In comparison with starting PORT 5 to 6 weeks postoperatively, initiating PORT earlier was not associated with improved survival (aHR for ≤ 4 weeks, 0.93; 99% CI, 0.85‐1.02; aHR for 4‐5 weeks, 0.92; 99% CI, 0.84‐1.01). Increasing durations of delay beyond 7 weeks were associated with small, progressive survival decrements (aHR, 1.09, 1.10, and 1.12 for 7‐8, 8‐10, and >10 weeks, respectively). CONCLUSIONS: Nonadherence to NCCN guidelines for initiating PORT within 6 weeks of surgery was associated with decreased survival. There was no survival benefit to initiating PORT earlier within the recommended 6‐week timeframe. Increasing durations of delay beyond 7 weeks were associated with small, progressive survival decrements. Cancer 2017;123:4841‐50 . © 2017 American Cancer Society . Abstract : In a review of patients with head and neck cancer in the National Cancer Data Base, nonadherence to National Comprehensive Cancer Network guidelines for initiating postoperative radiation therapy within 6 weeks of surgery is associated with decreased survival. There is no overall survival benefit to initiating postoperative radiation therapy earlier within the recommended 6‐week timeframe; increasing durations of delay beyond 7 weeks are associated with small progressive survival decrements.